ANALISIS FAKTOR PENENTU KEPUTUSAN KONSUMEN MUSLIM DALAM MEMILIH JASA PERBANKAN: BANK SYARIAH VS BANK KONVENSIONAL - ELA PATRIANA; NURISMALATRI NURISMALATRI (Prodi Manaj. Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam – UIN Imam Bonjol Padang, 2018)
The purpose of this study is to analyze the factors that influence the choice of Muslim customers against sharia banks and conventional banks. The object of research is sharia bank and conventional bank in Tangerang Selatan area. Data were collected through questionnaires. From the research result, there are four determinants of customer decision in sharia bank are: factor 1 (process), factor 2 (assurance), factor 3 (intense to use) and factor 4 (promotion). Factors influencing the decision to choose a conventional bank product are: factor 1 (reliability), factor 2 (people), factor 3 (feeling) and factor 4 (promotion). Bank service quality measurement is expected to provide useful information for bank management to improve and improve service quality to customers.